Recent nanoengineered therapeutic advancements in sepsis management - Liu, Li; Li, Li; Wang, Ting; Li, Zheyu; Yan, Bingpeng; Tan, Ruirong; Zeng, Anqi; Ma, Wenbo; Zhu, Xin; Yin, Zhujun; Ma, Chunhua (Frontiers in Bioengineering and Biotechnology, 2024)
Sepsis (defined as sepsis 3.0) is a life-threatening organ dysfunction caused by a dysregulated host response to a variety of pathogenic microorganisms. Characterized by high morbidity and mortality, sepsis has become a global public health problem. However, there is a lack of appropriate diagnostic and therapeutic strategies for sepsis and current management rely on the limited treatment strategies. Recently, nanomedicines targeting and controlling the release of bio-active agents have shown excellent potency in sepsis management, with improved therapeutic efficacy and reduced adverse effects. In this review, we have summarized the advantages of nanomaterials. Also, the preparation and efficacy of the main categories of anti-sepsis nanomedicines applied in sepsis management are described in detail, including antibiotic-coated nanomaterials, antimicrobial peptides-coated nanomaterials, biomimetic nanomaterials, nanomaterials targeting macrophages and natural products loaded nanomaterials. These advances in nanomedicines establish the huge potential for nanomaterials-based sepsis management, especially in the improved pharmaceutical and pharmacological properties, enhanced therapeutic efficacy, controllable drug-targeting and reduced side effects. To further facilitate clinical translation of anti-sepsis nanomedicines, we propose that the issues involving safety, regulatory laws and cost-effectiveness should receive much more attention in the future.